Wittgenstein's investigations 1-133 : a guide and interpretation - Lugg, Andrew, 1942- (Routledge, 2000)
This book provides an invaluable guide to the early sections of Wittgenstein's Philosophical Investigations - one of the greatest and most controversial works of twentieth century philosophy.